1998
DOI: 10.1084/jem.187.7.985
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammation and Susceptibility to Bacterial Infections in Mice Lacking the Polypeptide (p)105 Precursor (NF-κB1) but Expressing p50

Abstract: The polypeptide (p)50 molecule, a subunit of nuclear factor (NF)-κB, is produced after proteolytic processing of the p105 precursor (NF-κB1). Although the p105 precursor has been postulated to play a role in the regulation of the Rel/NF-κB activity, its physiological relevance remains unclear. To investigate that, we generated mutant mice lacking the COOH terminal half of the p105 precursor, but expressing the p50 product (p105−/−). These mutant mice displayed an inflammatory phenotype composed of lymphocytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 52 publications
(92 reference statements)
7
98
1
1
Order By: Relevance
“…nfkb2 DCT/DCT mice. Like the nfkb1 DCT/DCT mice (Ishikawa et al, 1998), targeted deletion of the p100 C-terminal ankyrin repeats reveals their importance as an inhibitory domain. Mice homozygous for this C-terminal deletion (nfkb2 DCT/DCT ) develop a wide range of postnatal pathologies that include gastric hyperplasia, hyperkeratosis in the heart and spleen, lymphocytic infiltrates of various tissues, enlarged lymph nodes and granulocytosis (Ishikawa et al, 1997).…”
Section: Nf-kb P52/p100mentioning
confidence: 96%
See 1 more Smart Citation
“…nfkb2 DCT/DCT mice. Like the nfkb1 DCT/DCT mice (Ishikawa et al, 1998), targeted deletion of the p100 C-terminal ankyrin repeats reveals their importance as an inhibitory domain. Mice homozygous for this C-terminal deletion (nfkb2 DCT/DCT ) develop a wide range of postnatal pathologies that include gastric hyperplasia, hyperkeratosis in the heart and spleen, lymphocytic infiltrates of various tissues, enlarged lymph nodes and granulocytosis (Ishikawa et al, 1997).…”
Section: Nf-kb P52/p100mentioning
confidence: 96%
“…Targeted deletion of the p105 C-terminal ankyrin repeats, which leads to elevated levels of nuclear p50 homodimers, confirms the importance of the C terminus as a regulatory domain. Animals homozygous for this mutation (nfkb1 DCT/DCT ) exhibit splenomegaly, enlarged lymph nodes and lymphoid infiltrates in various organs (Ishikawa et al, 1998). An increase in the number of B cells is accompanied by hyperresponsiveness to mitogens.…”
Section: Nf-kb P50/p105mentioning
confidence: 99%
“…Havard et al (2005) observed high levels of NF-kB p105 precursor in cell lines derived from human cervical cancers associated with HPV16 infection and in keratinocytes transfected by oncogenes. In another study, Ishikawa et al (1998) observed that NF-kB p105À/À mice showed abnormalities such as inflammation in lungs and liver, myeloid hyperplasia in bone marrow and splenomegaly (Weih et al, 1994). In a study that included 45 patients with NSCLC, Zhang et al (2006) found overexpression of NF-kB p50 to indicate an unfavourable overall survival in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ishikawa et al (46) studied a mouse model in which the genetically engineered NF-B1 locus directly produces the mature p50 subunit instead of the p105 precursor. In these animals, a dramatic increase in the nuclear p50 homodimer was observed, and yet expression of a number of NF-B target genes, including CSF-1, actually increased.…”
Section: Discussionmentioning
confidence: 99%